Effects of Salting Pretreatment on Quality and Safety of Shrimp (Parapenaeopsis Spp.) Powder. - Abdullah Zawawi, Nur Farhanis; Ramli, Nor Aisyah; Yusoff, Nur Nadhila Elisa; Tang, John Yew Huat; Abd Ghani, Asmaliza (Journal of Applied Food Technology, 2023)
Shrimps are well known as one of the healthiest seafood options, providing a huge amount of protein, vitamins, and minerals. However, shrimp is a highly perishable food, thus attempts to make innovative and healthy products may improve per capita consumption while lengthening the nutrient content shelf life. This research focused on the effects of different pretreatment salt concentrations at 0, 3, 6, and 9% on nutritional composition, microbial activity, and sensory evaluation of the shrimp powder samples. The analyses were performed in triplicate using the Association of Official Analytical Chemicals (AOAC) method for proximate analysis and physical analysis was used to determine pH, color, and water activity. The sensory attributes like saltiness, color, odor, texture, and aftertaste were measured using the hedonic scale method. Initial findings demonstrated significant differences in proximate composition, particularly protein content, ranging from 13 to 46% (w/w). There were also notable variations in color attributes among the shrimp powder samples. The lightness value varied, reflecting differences in the brightness levels of the powder, ranging from light to dark shades. The findings also revealed there were no significant differences in the total plate count among the shrimp powder samples which ranged from 3.50 to 2.69 Log CFU/g except shrimp powder treated with 0% salt concentration sample exhibited slightly higher counts compared to others which is 4.93 Log CFU/g. Sensory evaluation revealed variations in saltiness, color, odor, texture, and aftertaste profiles, with certain samples exhibiting stronger saltiness, color, odor, texture, and aftertaste, while others had milder attributes. These findings show that the most preferable salt concentration for brining shrimp is 3% because it can preserve protein content and have the best acceptability during sensory evaluation.